Shelf life study of chilled microwavable dinuguan - Pasco, May Anne R.; Villarino, Blanca J. (2001., 2001)
The main concern of this study was to establish the shelf life of chilled microwavable dinuguan. The microwave time and temperature/power combination was established using sensory evaluation and microbial analysis. The microwave time and temperature/power of 6 minutes at Power 7 without stirring was chosen as the combination that gave the optimum quality of the product closest to the conventionally cooked dinuguan. Microbial analysis showed that this was sufficient to destroy microorganisms in the product that can affect its quality and shelf life. The results were analyzed using General Linear Model Multivariate under ANOVA. Actual shelf life study was conducted using microbiological analysis and sensory evaluation. The microbiological analysis showed no significant microbial growth until 21st sampling day where the E. coli growth exceeded the standard acceptable count to coliform. The sensory attributes increased in their rating and acceptability as the storage study proceeds. The shelf life was estimated at 19 days based on the microbial and sensory analysis. At this number of days, the product was still safe and the microbial counts were all still below the standard count. The sensory attributes were also still acceptable.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Convenience food; Meat and meat products